Vertical integration and servitization strategies for a container liner How to compete for customers in a market of overcapacity - Kjellberg, Leif; Gerxhaliu, Kastriot (My University, 2020)
Shipping industry is cyclical in nature and freight rates can fluctuate volatilely. There is also a risk for sudden overcapacity, especially if lag in construction of new vessels results in release at a time when demand is lower. There are reports from 2019 that show an overcapacity within the industry and it has been reported that vertical integration is increasing in favor of building more and larger size container vessels. Media is reporting that major container liners are investing in terminals, forwarding companies, airlines and service companies worldwide. They have also started offering more and more services and initiated digital platform within supply chain. There are also reports on automation and efforts to automate ships and cargo handling to an as large extend as possible. This is in line with what other industries are doing today within digitalization, automation and servitization. However, the question remains what their strategies with vertical integration and servitization are, and how will container shipping evolve. Using qualitative methods and observations, this study aims to discover the strategies followed by the container liners today to enhance their competitiveness in an oversupplied market. Findings in this study indicates that the major container liners are seeking competitive benefits from buyer selection. This implies that the customer ultimately loses bargaining power and that, for example, high negotiation costs can be reduced or kept at a minimum. Buyer selection is a relatively broad subject and it is elaborated in various theories about competition and competition strategies. It means that the customer loses bargaining power, however increased buyer selection does not necessarily have a direct negative impact for the customer.
Keywords: Container liner, Sea freight, Container freight, Container services, Automation, Digitalization, Servitization, Vertical integration, Competition